Assay of CB1 Receptor Binding - Catani, Valeria M; Gasperi, Valeria (Methods in molecular biology (Clifton, N.J.), 2016)
Type-1 cannabinoid receptor (CB1), one of the main targets of endocannabinoids, plays a key role in several pathophysiological conditions that affect both central nervous system and peripheral tissues. Today, its biochemical identification and pharmacological characterization, as well as the screening of thousands of novel ligands that might be useful for developing CB1-based therapies, are the subject of intense research. Among available techniques that allow the analysis of CB1 binding activity, radioligand-based assays represent one of the best, fast, and reliable methods.Here, we describe radioligand binding methods standardized in our laboratory to assess CB1 binding in both tissues and cultured cells. We also report a high-throughput radioligand binding assay that allows to evaluate efficacy and potency of different compounds, which might represent the basis for the development of new drugs that target CB1 receptor-dependent human diseases.